(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The research focused on providing motorcycle drivers with a safe way to drive during bad weather. The study showed the effectiveness of helmets with wipers for the safety of grade 12 Accountancy, Business, and Management (ABM) Strandstudents of Bestlink College of the Philippines who are motorcycle riders. Motorcycles are different from other cars that are fully covered and protected. Hence, during the rainy season, motorcycle drivers have difficulties in driving due to heavy rains. Cars have wipers that help the driver to see clearly when raining, but motorcycles do not have wipers. Thus, we decided to put wipers in the helmet to allow riders to see clearly when raining. Wearing a helmet can reduce the risk of serious brain injury and death due to a fall or collision because most of the impact is absorbed by the helmet. This study is important because it talks about people’s safety when riding a motorcycle. The objectives of this study were to help people, especially motorcycle drivers, by creating helmets with wipers to prevent the brain from damage in an accident during the rainy season. A qualitative method was used in this action research by using the descriptive research design. This study involved 50 selected motorcycle riders from grade 12 ABM Strandstudents. We chose the qualitative design because we want to answer the whys and hows of the phenomenon in question. Four variables were considered regarding the effectiveness of helmets with wipers, such as effects of raindrops on drivers, the importance of helmets with wipers, precautionary measures during rainy days, and ways to prevent motorcycle accidents. Rainy season or bad weather is a huge risk for motorcycle rider’s safety. The results revealed that students look forward to and trust the helmet wiper as safety gear to prevent an accident. According to the respondents, it is easier to drive when raining because they can see the road even during bad weather. The study revealed that the helmet with wiper is effective in ensuring the safety of motorcycle riders. The study also showed the advantages of using a helmet with a wiper to ensure safety or prevent serious injuries. This result also showed the effectiveness of helmets with wipers that are used in other countries with solid results, feedback, and a basis for further innovation.